(3GdYbO GdKejf aj JGQjN GdHdO GdCejfs - (3Jbi GdOjf eMeO Hf eMeO Hf CMeO Hf Ydj GdMSfj GdaGSi Gdecj,J (B832 (3g` s
(3ChdgG (B:s
(3jHJOF HYGHS ehdi MhjWH ef MQa GdYjf s
(3BNQgG (B:s
(3jfJgi HYjjSi Hf jRjO GdLdhOi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B331 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B300s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B173 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B182 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1150s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B6(3b(B) s
Keywords: (3GdJGQjNs